Main inclusions and general and property modifications to the Book X: International Private Law - Delgado Barreto, César (2014)
International Private Law has gone through several changes and modifications, in step with the globalization phenomenon, for whichthe  relations  between  citizens of  different countries have become more frequent and complex. In that regard, it is necessary to ask how International Private Law should react tobe in accordance with the new scenarios.In this article, the author examines the general and patrimonial aspects of International Private Law that he considers must be redefined, comparing the current dispositions of the Peruvian Civil Code with international regulations and national reform projects, and introducing a modification proposal for each topic.